PENGARUH MODEL COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP KECERDASAN INTERPERSONAL PADA MATA PELAJARAN IPS - anti, Mari; Susanto, Ratnawati (Jurnal Ilmiah Sekolah Dasar, 2017)
Interpersonal intelligence is one of the goals in elementary school education. Interpersonal intelligence is a key element in the adaptation of children in their social relationships. SDN Kebon Jeruk 11 Pagi West Jakarta found a number of 19 students of 30 children (63%) have barriers Interpersonal intelligence. Quantitative Research with One Shot Case Study Experiment using sample saturated with size 30 in research influence influence model cooperative learning type Teams Games Tournament (TGT) to interpersonal intelligence. The results of this study prove that: The more effective the steps of cooperative learning model type TGT done then the better the interpersonal intelligence. So in this research result that model Cooperative Learning type Teams Games Tournament (TGT) have positive effect to interpersonal intelligence.